Relationship Between Andean Knowledge and the Quechua Language Among Peruvian University Students as a Resource for Cultural Resistance (Islas, 2025)
Introduction: The challenges threatening the preservation and revitalization of Quechua culture require actions that unite efforts among its different components. In this context, the relationship between Andean knowledge and the Quechua language among university students represents an expression of a collective construct essential for the preservation and intergenerational transmission of the Quechua worldview.Methods: This research followed a mixed-methods, non-experimental, and correlational approach. Based on an ethnographic design, it seeks to establish the statistical relationship between the variables of Andean knowledge and the Quechua language, and, on that basis, to provide a qualitative interpretation of the results.Results: Significant correlations were found between all dimensions of Andean knowledge and Quechua language proficiency, with Andean technology showing the highest correlation coefficient (r = 0.905, p = 0.000). These findings suggest a significant relationship between ancestral practices and proficiency in the Quechua language, which can be employed as a resource for cultural resistance and the preservation of Quechua culture.Conclusion: The preservation of Quechua culture must be a joint effort among communities, educational institutions, and public policies, leveraging the various components that comprise it in order to revitalize this complex cosmovisive framework and thereby contribute significantly to the preservation and enjoyment of this culture.
Keywords: andean knowledge; quechua language; cultural identity; quechua culture; cultural resistance